Lesbian, Gay and Bisexual Clients’ Experiences of Discussing Sexual Identity in Therapy - Tsai, Sandy (Auckland University of Technology, 2013)
The current study explores lesbian, gay and bisexual (LGB) individuals’ experiences of discussing sexual identity in therapy. Current literature indicate that the absence of sexual identity issues being identified and discussed could be a significant barrier to effective therapy with LGB clients. However, little research has explored how sexual identity is conceptualized in therapy by LGB clients and their therapists, and how this influences their therapeutic outcomes. Using interpretative phenomenological analysis (IPA), LGB clients’ experiences of discussing sexual identity in therapy was investigated. Results clustered into three overarching themes: 1. Sexual identity as self in the making; 2. Sexual identity as a barrier; and 3. Sexual identity as increased awareness of oppression. Discussion of sexual identity is important for LGB clients in therapy, regardless of whether it is the main focus of their presenting issues. These discussions help them explore their sexual identity formation processes, which result in a stronger sense of identity due to a better understanding of sexual identity as an aspect of themselves. LGB clients who lack such opportunities to discuss sexual identity in therapy experience heteronormative assumptions and biases from their therapists, which increased their awareness of themselves as individuals of sexual minority and empathy towards others under oppression. The current study concludes that therapists should remain open-minded and explorative when helping LGB clients discuss their sexual identities in therapy, but always in context to their presenting issues so that conceptualizations and sense-making of sexual identity is centred in the clients’ subjective experiences
Keywords: Homosexuality; Therapy; Gay; Lesbian; Bisexual